2020
DOI: 10.30773/pi.2020.0127
|View full text |Cite
|
Sign up to set email alerts
|

The Anxiety Status of Chinese Medical Workers During the Epidemic of COVID-19: A Meta-Analysis

Abstract: Objective To analysis the anxiety status of Chinese medical workers during the epidemic of COVID-19 by meta-analysis method. Methods CNKI, VIP, WanFang Data, SinoMed, PubMed, Cochrane, EMBASE, MEDLINE, Scopus, Google Scholar and other databases were searched to collect literature on the anxiety status of Chinese medical workers during the epidemic of COVID-19. The retrieval time is from the database construction to 11/03/2020. Meta-analysis was performed on the included articles by using Stata 16.0 software. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 27 publications
5
64
0
12
Order By: Relevance
“…This trend is characteristic not only for medical workers in Russia, but also for India[ 14 ] and China. [ 15 16 ] In the second stage of our study, this was confirmed by a decrease in the frequency of media requests by respondents. It is important that with a decrease in the levels of psychological stress, the scores of devaluation/discrimination increased among medical workers over time.…”
Section: Discussionsupporting
confidence: 70%
“…This trend is characteristic not only for medical workers in Russia, but also for India[ 14 ] and China. [ 15 16 ] In the second stage of our study, this was confirmed by a decrease in the frequency of media requests by respondents. It is important that with a decrease in the levels of psychological stress, the scores of devaluation/discrimination increased among medical workers over time.…”
Section: Discussionsupporting
confidence: 70%
“…Other literature reviews of previous epidemics and/or the COVID-19 pandemic have focused on generic psychological distress and/or anxiety and depressive symptoms. Meta-analyses have found a high prevalence of anxious and depressive symptoms among HCWs, especially among women and nurses (Pan et al, 2020;Pappa et al, 2020). In addition, a series of recent reviews highlighted that risk factors, such as being female, younger, being a nurse, lack of adequate protective equipment, and exposure to infected people, have been found to be associated to TRSs in previous epidemics (Brooks S. K. et al, 2020;Kisely et al, 2020;Rajkumar, 2020;Spoorthy, 2020;Walton et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews have explored social and occupational factors associated with psychological outcomes in HCW during an infectious disease outbreak ( Brooks et al 2018 ), and their perceptions of risk and use of coping strategies towards emerging respiratory infectious diseases ( Koh et al 2011 ). A number of recent systematic reviews have examined the psychological and mental impact of COVID-19 on medical staff and other HCWs ( Garcia-Iglesias et al 2020 , Kisely et al 2020 , Luo et al 2020 , Pan et al 2020 , Pappa et al 2020 , Shaukat et al 2020 ), some of them focussing on specific mental health problems such as post-traumatic stress disorder (PTSD) ( Carmassi et al 2020 ) or anxiety ( Pan et al 2020 ). However, given the exponential proliferation of studies on this area during the last months, there is a need to synthesise the current body of knowledge.…”
Section: Introductionmentioning
confidence: 99%